KESADARAN WAJIB PAJAK, SANKSI WAJIB PAJAK DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KENDARAAN BERMOTOR DI KOTA MALANG - Edi - Sudiarto (STIE Malangkucecwara Malang) (STKIP PGRI TULUNGAGUNG, 2020)
AbstractThis study aimed to examine the effect of the taxpayer awareness, knowledge of the taxpayer, on tax compliance and taxpayer sanctions on taxpayer compliance. The population is all taxpayers registered in SAMSAT Malang and the sample used is 100 respondents. While the data collection method is by distributing questionnaires. The results showed there was a significant effect between taxpayers awareness on tax compliance, significant influence of taxpayer sanctions on taxpayer compliance and a significant effect of taxpayer knowledge on taxpayer complianceKeywords: taxpayer awareness, knowledge taxpayer, tax compliance